Implementasi Media Simulasi PhET untuk Meningkatkan Keterampilan Proses Sains pada Materi Suhu dan Kalor - Yulia Kuttayyibatun Nisa'; Aris Rudi Purnomo (PendIPA Journal of Science Education, 2026)
Science learning emphasizes not only conceptual understanding but also the development of science process skills (SPS). However, limited laboratory facilities and conventional teaching methods often hinder the optimal development of students’ SPS, especially in abstract topics such as temperature and heat. This study aimed to improve students’ science process skills through the implementation of PhET simulation media on temperature and heat materials. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The study was conducted at SMP Negeri 5 Pamekasan during the odd semester of the 2025/2026 academic year, involving 30 seventh-grade students as research subjects. Data collection techniques included science process skills tests, learning implementation observation sheets, and student response questionnaires. Research instruments consisted of pretest–posttest questions, observation sheets, and Likert-scale questionnaires. Data analysis was performed using normalized gain (N-gain) analysis and descriptive statistical analysis. The results showed that the implementation of PhET simulation media effectively improved students’ science process skills on temperature and heat materials, with a moderate to high category of improvement. In addition, students provided positive responses toward the use of PhET simulations in learning activities. It can be concluded that PhET simulation media is effective as an alternative learning media to enhance science process skills. Therefore, teachers are recommended to integrate PhET simulations into science learning to support active and meaningful learning experiences